Analysis of Digital Marketing Strategies to Consolidate Sustainable Tourism: Case study of the Manga del Mar Menor. - Alcolea Parra, María; Bastidas Manzano, Ana Belén; Sánchez González, Olga (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Sustainable tourism is a challenge faced by all tourist destinations. Specifically, La Manga del Mar Menor is a destination with natural resources that have been affected in recent years by mining and tourism pressures. Although there are numerous studies that contemplate this destination, none focuses on sustainable tourism marketing through an analysis of tourism promotion campaigns on television and social networks (2019-2023), pre-pandemic and post-pandemic. The purpose of this article's contribution is to be a synergy between sustainable marketing and tourism destination planning.